Rancang Bangun Ensiklopedia Tanaman Obat Berbasis Semantik Web - Putra, Febri Pradana; Jusak, Jusak; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Indonesia a rich country in a wide range of plant includes various types of medicinal plants. However, the lack of media information which presents knowledge of that information cause ignorance among the public. The problem faced in documentation of knowledge on medicinal plants stand on the biological data which is complex and heterogeneous due to derived from a variety of sources of research and the use of the terms used is also different. With the implementation of this technology expected to be able maximize the presentation of information so that it makes encyclopedias app users to obtain the desired information.